2016
DOI: 10.1371/journal.pone.0159456
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotypic Effects of Royal Jelly on Wild-Type D. melanogaster Are Strain-Specific

Abstract: The role for royal jelly (RJ) in promoting caste differentiation of honeybee larvae into queens rather than workers is well characterized. A recent study demonstrated that this poorly understood complex nutrition drives strikingly similar phenotypic effects in Drosophila melanogaster, such as increased body size and reduced developmental time, making possible the use of D. melanogaster as a model system for the genetic analysis of the cellular mechanisms underlying RJ and caste differentiation. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Rearing flies at different densities influences not only the final body size of eclosed flies, but also the size of their internal organs (Mirth and Shingleton 2012), including the primary and secondary organs of the male reproductive system (Morimoto et al 2022). Experimentally increasing larval density leads to progressively smaller males who developed larger testes and ejaculatory ducts, but smaller accessory glands and ejaculatory bulbs (Morimoto et al 2022). Morrow et al (2008) found that the production of sperm cells was affected both by a fly's genotype as well as the nature of the environment it developed in.…”
Section: Discussionmentioning
confidence: 99%
“…Rearing flies at different densities influences not only the final body size of eclosed flies, but also the size of their internal organs (Mirth and Shingleton 2012), including the primary and secondary organs of the male reproductive system (Morimoto et al 2022). Experimentally increasing larval density leads to progressively smaller males who developed larger testes and ejaculatory ducts, but smaller accessory glands and ejaculatory bulbs (Morimoto et al 2022). Morrow et al (2008) found that the production of sperm cells was affected both by a fly's genotype as well as the nature of the environment it developed in.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic outcomes depend absolutely on the genetic background used in the experiments 5557 . As just one clear example reveals, in mushroom body miniature , these important brain structures in the fly degenerate in one genetic background, but are completely normal in another 58 .…”
Section: Caste Determination As An Epigenetic Developmental Processmentioning
confidence: 99%
“…Seventh, Drosophila is indeed facile in terms of experimental manipulation, but it has major drawbacks that impinge upon data transferability (e.g., the lack of DNA methylation toolkit and reproductive division of labour 54 ). Phenotypic outcomes depend absolutely on the genetic background used in the experiments 55 57 . As just one clear example reveals, in mushroom body miniature , these important brain structures in the fly degenerate in one genetic background, but are completely normal in another 58 .…”
Section: Caste Determination As An Epigenetic Developmental Processmentioning
confidence: 99%
See 2 more Smart Citations